Temporal Changes of Seismic Velocity Caused by Volcanic Activity at Mt. Etna Revealed by the Autocorrelation of Ambient Seismic Noise - De Plaen, Raphael S. M.; Cannata, Andrea; Cannavo', Flavio; Caudron, Corentin; Lecocq, Thomas; Francis, Olivier (Frontiers in Earth Science, 2019)
On active volcanoes, ambient noise-based seismic interferometry can be a very useful monitoring tool as it allows to detect very slight variations in seismic velocity associated with magma transported toward the surface. However, the classical cross-station approach occasionally fails to detect seismic velocity changes related to eruptive activity, even on very active, well-instrumented volcanoes such as Mt. Etna. In this work, we explored an improved ambient noise-based monitoring strategy by performing the autocorrelation of seismic noise recorded at Mt. Etna volcano, by three stations located close to the active summit craters, during April 2013–October 2014. Such an interval was chosen because of the number and variety of eruptions. In place of the classical cross-correlation, we implemented the phase cross-correlation of each component with itself, which does not require normalization of the signals. The detected seismic velocity variations were very consistent for all three stations throughout the study period, mainly ranging between 0.3 and −0.2%, and were time-related to both sequences of paroxysmal eruptions and more effusive activities. In particular, we observed seismic velocity decreases accompanying paroxysmal eruptions, suggesting an intense pressurization within the plumbing system, which created an area of extensional strain with crack openings. In addition, seismic velocity variations over time were analyzed in the light of ground deformation data recorded by GPS stations and volcanic tremor centroid locations and displayed a particularly strong correlation with the former. Finally, we showed that, although the investigated frequency band (1–2 Hz) contained most of the volcanic tremor energy, our results did not indicate a particular contamination of seismic velocity variation measurements by variations of tremor sources. Ultimately, our investigation highlights a better way to implement noise-based seismic monitoring techniques. The near-field sensitivity of the autocorrelation helped improve our understanding of the relationship between variations of seismic velocity, ground deformation and the pressurization dynamics of volcanic plumbing systems which, in turn, allows for better monitoring implementations of seismic interferometry on other volcanoes.